Everyone's Invited: Have we done enough?. (2nd May 2021) - Rose, Elizabeth
Abstract : The Everyone's Invited revelations and Ofsted's review of sexual harassment and abuse in schools has clear implications for safeguarding practice. Elizabeth Rose advises how we can review our safeguarding structures around sexual harassment, violence and abuse